Coefficient of Lateral Deformation and Volume Deformation of Frozen Soils in the Creep Process (O Koeffitsiente Poperechnoi Deformatsii i Ob Obemnykh Deformatsiykh Merzlykh Gruntov v Protsesse Polzuchesti) - Shusherina,E. P. (1970)
The article is a review of experimental data characterizing the lateral deformation coefficient for frozen soils in the creep process; these data are analyzed in relation to volume deformations. The article was written using data obtained by the author in the Permafrost Department of Moscow State University during 1958-59. (Author) Trans. of Merzlotnye Issledovaniya (USSR) n4 p229-240 1966.